Center of pressure-based postural sway differences on parallel and single leg stance in Olympic deaf basketball and volleyball players - Makaraci, Y.; Soslu, R.; Özer, Ö.; Uysal, A. (Journal of Exercise Rehabilitation, 2021)
In sports such as basketball and volleyball, loss of balance due to the inability to maintain body stability and lack of postural control adversely affect athletic performance. Deaf athletes appear to struggle with balance and postural stability problems. The purpose of this study was to examine postural sway values in parallel and single leg stance of Olympic deaf basketball and volleyball players and reveal differences between the branches. Twenty-three male athletes from the Turkish national deaf basketball (n=11) and volleyball (n=12) teams participated in the study. After anthropometric measurements, the subjects completed postural sway (PS) tests in parallel/single leg stances with open eyes and closed eyes on a force plate. PS parameters (sway path, velocity, and area) obtained from the device software were used for the statistical analysis. The Mann-Whitney U-test was used to compare differences in PS parameters between basketball and volleyball players, and the alpha value was accepted as 0.05. Volleyball players had significantly better results in parallel stance and dominant leg PS values than basketball players (P<0.05). There was no significant difference between the groups in nondominant leg PS values (P>0.05). We think that proprioceptive and vestibular system enhancing training practices to be performed with stability exercises will be beneficial in terms of both promoting functional stability and interlimb coordination. Trainers and strength coaches should be aware of differences in the postural control mechanism of deaf athletes.